Gene Therapy for Human Sensorineural Hearing Loss - Ren, Yin; Landegger, Lukas D.; Stankovic, Konstantina M. (Frontiers in Cellular Neuroscience, 2019)
Hearing loss is the most common sensory impairment in humans and currently disables 466 million people across the world. Congenital deafness affects at least one in 500 newborns, and over 50% are hereditary in nature. To date, existing pharmacologic therapies for genetic and acquired etiologies of deafness are severely limited. With the advent of modern sequencing technologies, there is a vast compendium of growing genetic alterations that underlie human hearing loss, which can be targeted by therapeutics such as gene therapy. Recently, there has been tremendous progress in the development of gene therapy vectors to treat sensorineural hearing loss in animal models in vivo. Nevertheless, significant hurdles remain before such technologies can be translated towards clinical use. These include addressing the blood-labyrinth barrier (BLB), engineering more specific and effective delivery vehicles, improving surgical access, and validating novel targets. In this review, we both highlight recent progress and outline challenges associated with in vivo gene therapy for human sensorineural hearing loss.